2020
DOI: 10.17358/jma.17.2.196
|View full text |Cite
|
Sign up to set email alerts
|

The The Effects of Entrepreneurial Behavior on Seaweed Business Performance in Takalar Regency

Abstract: Seaweed is one of the main aquaculture products which has high economic value and serves as strategic business opportunities. Seaweed farming becomes the main livelihood for people in Takalar Regency, so it is necessary to improve the working quality of seaweed farmers through the development of entrepreneurial behavior as a new variable in improving the performance of seaweed business. This research is intended to examine the effects of the environment on farmers' entrepreneurial behavior and the effects of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…In contrast, environmental factors do not substantially influence entrepreneurial behavior. This matter is in line with Siahaan (2019) and Syam (2020) research that individual factors have a significant effect on entrepreneurial behavior, but the business environment elements from each of Siahaan and Syam's research have no substantial and negative impact on entrepreneurial behavior. However, the central hypothesis of this study is that entrepreneurial behavior has a positive and significant effect on the performance of salt ponds in Jeneponto Regency, South Sulawesi.…”
Section: The Effect Of Individual Characteristics and Business Enviro...supporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, environmental factors do not substantially influence entrepreneurial behavior. This matter is in line with Siahaan (2019) and Syam (2020) research that individual factors have a significant effect on entrepreneurial behavior, but the business environment elements from each of Siahaan and Syam's research have no substantial and negative impact on entrepreneurial behavior. However, the central hypothesis of this study is that entrepreneurial behavior has a positive and significant effect on the performance of salt ponds in Jeneponto Regency, South Sulawesi.…”
Section: The Effect Of Individual Characteristics and Business Enviro...supporting
confidence: 81%
“…Individual and environmental factors also influence the entrepreneurial behavior of gayo arabica coffee producers, and entrepreneurial behavior has a positive and significant impact on the performance perspective of gayo arabica coffee production. In line with this, Amir et al (2018) and Syam et al (2020) found that entrepreneurial behavior positively affects firm performance. Entrepreneurial behavior is reflected in four indicators: responsiveness to opportunities, innovation, courage to take risks, and business activities (Amir et al 2018).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Because business owners have a role in controlling business operations so that business goals are achieved as much as possible, business capabilities and characteristics significantly impact MSEs. In line with that, Amir et al (2018) and Syam et al (2020) found that entrepreneurial behavior positively affects business performance. Entrepreneurial behavior is reflected by four indicators: responsiveness to opportunities, innovation, daring to take risks, and active business (Amir et al 2018).…”
Section: Introductionsupporting
confidence: 71%